2021
DOI: 10.1002/stem.3383
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Revisiting Nodal Signaling in Human Pluripotent Stem Cells

Abstract: Nodal is a transforming growth factor-β (TGF-β) superfamily member that plays a number of critical roles in mammalian embryonic development. Nodal is essential for the support of the peri-implantation epiblast in the mouse embryo and subsequently acts to specify mesendodermal fate at the time of gastrulation and, later, left-right asymmetry. Maintenance of human pluripotent stem cells (hPSCs) in vitro is dependent on Nodal signaling. Because it has proven difficult to prepare a biologically active form of reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 82 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…53,54 To better understand the cell viability improvement by resveratrol during ETEC K88 infection, we also detected the gene expression of TGFB1 and KLF4, two important markers for cell growth and differentiation. 55,56 Consistent with the reduction of cell viability, ETEC K88 treatment decreased the gene expression of TGFB1 and KLF4, which was reversed by resveratrol pretreatment, indicating that IPEC-1 cells supplied with resveratrol gained a greater ability to deal with ETEC K88 infection. Moreover, our research suggested that resveratrol protected tight junctions at mRNA and protein levels in ETEC K88treated cells.…”
Section: Papermentioning
confidence: 72%
“…53,54 To better understand the cell viability improvement by resveratrol during ETEC K88 infection, we also detected the gene expression of TGFB1 and KLF4, two important markers for cell growth and differentiation. 55,56 Consistent with the reduction of cell viability, ETEC K88 treatment decreased the gene expression of TGFB1 and KLF4, which was reversed by resveratrol pretreatment, indicating that IPEC-1 cells supplied with resveratrol gained a greater ability to deal with ETEC K88 infection. Moreover, our research suggested that resveratrol protected tight junctions at mRNA and protein levels in ETEC K88treated cells.…”
Section: Papermentioning
confidence: 72%
“…6f, g ). Similarly, the expression of BMP4, NODAL and CRIPTO (a NODAL co-receptor 35 , 48 ) was unchanged in GPC4sh (Supplementary Fig. 6f, g ).…”
Section: Resultsmentioning
confidence: 91%
“…To trigger hiPSC differentiation along these lineages we exposed cells to BMP4 and ACTIVIN A (Fig. 2c), a commonly used surrogate to activate aspects of the NODAL signaling pathway in vitro [33][34][35][36][37] . We then evaluated the differentiation profile of control and GPC4sh hiPSCs by using RT-qPCR analysis following lineage-specific markers.…”
Section: Enhanced Mesendoderm Fate Acquisition In Gpc4sh Culturesmentioning
confidence: 99%
“…Pathway enrichment in whole blood showed pathways involved in biogenesis of mitochondria, and fibronectin matrix formation. NODAL signaling was also upregulated in whole blood and is involved in maintaining the human pluripotent stem cell population 19 . Upregulation of pathways involved in inflammation were also shown, such as the AIM2 inflammasome 20 , which is involved in inflammatory signaling and inflammatory related apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…18 Pathway enrichment in whole blood showed pathways involved in biogenesis of mitochondria, and fibronectin matrix formation. NODAL signaling was also upregulated in whole blood and is involved in maintaining the human pluripotent stem cell population 19 .…”
Section: Discussionmentioning
confidence: 99%